2010
DOI: 10.1108/10595421011047433
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of poverty and consumption: the sustainability dilemma

Abstract: PurposeThe purpose of this paper is to discuss the dilemma of global sustainable economic development and poverty alleviation in the context of the environmental concerns.Design/methodology/approachA range of recently published literature focusing on the bottom of the pyramid (BoP) is reviewed. The arguments that are in favor and against the notion of poor being a “market” are examined. The implications of increased consumption by the poor even while the developed countries maintain their levels of consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Furthermore, those individuals who have a precarious financial and material standing are trapped into poverty and kept in this condition because their poor resource accessibility limits them to look for deficiently remunerated jobs, so rejoicing a decent existence is out of question for them. Two explanatory factors for this happening are the absence of basic living elements' ownership and the non-performance of national decisional institutions which do not properly address these issues (Farias and Farias, 2010). The absence of necessary living supplies is considered to have a bigger contribution to poverty development by Sachs (2005) who also states that the inefficient processes of decisional authorities are not entirely liable for this phenomenon but proposes shifting the ruling authorities' perspective of dealing with the social domain to foster people's thriving chances.…”
Section: Poverty and Social Exclusion As Social Misbalancesmentioning
confidence: 99%
“…Furthermore, those individuals who have a precarious financial and material standing are trapped into poverty and kept in this condition because their poor resource accessibility limits them to look for deficiently remunerated jobs, so rejoicing a decent existence is out of question for them. Two explanatory factors for this happening are the absence of basic living elements' ownership and the non-performance of national decisional institutions which do not properly address these issues (Farias and Farias, 2010). The absence of necessary living supplies is considered to have a bigger contribution to poverty development by Sachs (2005) who also states that the inefficient processes of decisional authorities are not entirely liable for this phenomenon but proposes shifting the ruling authorities' perspective of dealing with the social domain to foster people's thriving chances.…”
Section: Poverty and Social Exclusion As Social Misbalancesmentioning
confidence: 99%
“…Other studies discovered microfinance to improve consumption and per capital expenditure (Baktiari, 2006;Mawa, 2008;Afelunini & Wasowei, 2012). Farias and Farias (2010) concluded that microfinance providers in developed nations cannot sustain the microloans to the poor nations due to high level of consumption and the quest for the developed nations to maintain their high standard of living. On a contrary, Karlan and Zinman (2010) concluded that having access to credit do not lead to increase in profit of the businesses and household consumption.…”
Section: Effect Of Microfinance On Poverty Alleviationmentioning
confidence: 99%
“…However, despite the many precautions taken, it is seen that water is still being lost during its distribution. There have been many research studies conducted on the types of water losses, how water gets wasted due to leaks during daily activities [9], volume of water actually used as a percentage of the volume of the treated water [22] and the volume of nonrevenue water as a percentage of the total volume of treated water supplied [8]. There have been several studies to identify ways of saving water during day to day activities, ways of managing the available water resource in a sustainable way etc.…”
Section: Introductionmentioning
confidence: 99%